Frequency and Outcomes of Inferior Wall Myocardial Infarction without Left Dominant System - Aziz Ullah; Kamran Ahmed Khan; Ashraf Abdul Qahir (Indus Journal of Bioscience Research, 2025)
Background: Inferior wall myocardial infarction (IWMI) is a common type of ST-elevation myocardial infarction (STEMI), usually resulting from right coronary artery (RCA) occlusion in patients with a right-dominant coronary system. Objective: To determine the frequency and in-hospital outcomes of inferior wall myocardial infarction (IWMI) in patients with a non-left dominant coronary artery system. Methodology: This Descriptive observational study was conducted at National Institute of Cardiovascular Diseases (NICVD), Karachi, from 25th February 2025 to 1st June 2025. A total of 171 patients aged 18–70 years with acute IWMI and a non-left dominant coronary system were included through non-probability convenient sampling. Patients with prior myocardial infarction, cardiac revascularization, chronic kidney disease, or other major exclusions were omitted. Data were collected using a structured proforma. Results: Out of 171 patients, 138 (80.7%) presented with STEMI and RCA was the culprit vessel in 164 (95.9%). The most common lesion location was proximal RCA (51.5%) and Killip Class I was seen in 61.4% of patients. Right ventricular infarction occurred in 32.7%, complete heart block in 18.1%, advanced heart failure in 11.7%, and in-hospital mortality in 7.6% of cases. RV infarction was significantly associated with proximal RCA occlusion (p = 0.02) and CHB (p = 0.01). Patients with LVEF <30% had significantly higher mortality (p = 0.004). Conclusion: Patients with IWMI and non-left dominant systems predominantly have RCA involvement and carry substantial risk of conduction abnormalities and RV dysfunction. Early recognition and aggressive management are crucial to prevent adverse outcomes. Coronary dominance assessment should be a routine part of diagnostic angiography for better risk stratification.